2008
DOI: 10.1152/jn.01086.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Postsynaptic GABABReceptors Modulates the Bursting Pattern and Synaptic Activity of Olfactory Bulb Juxtaglomerular Neurons

Abstract: Olfactory bulb glomeruli are formed by a network of three major types of neurons collectively called juxtaglomerular (JG) cells, which include external tufted (ET), periglomerular (PG), and short axon (SA) cells. There is solid evidence that γ-aminobutyric acid (GABA) released from PG neurons presynaptically inhibits glutamate release from olfactory nerve terminals via activation of GABA B receptors (GABA B -Rs). However, it is still unclear whether ET cells have GABA B -Rs. We have investigated whether ET cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…In addition, the presence of GABA B Rs in neurons in the OB also has been demonstrated in rats (47). Interestingly, similar to the hypothalamus, GnRH content in OB was markedly decreased in adult female GABA B1 KOs but not in males.…”
Section: E690 Gnrh Expression and Physiology In Gabab1 Knockout Micementioning
confidence: 68%
“…In addition, the presence of GABA B Rs in neurons in the OB also has been demonstrated in rats (47). Interestingly, similar to the hypothalamus, GnRH content in OB was markedly decreased in adult female GABA B1 KOs but not in males.…”
Section: E690 Gnrh Expression and Physiology In Gabab1 Knockout Micementioning
confidence: 68%
“…These results do not exclude the possibility of additional tonic GABA B R inhibition at the ET3 PG synapse. However, while a recent study showed that ET cells have GABA B Rs that can be activated by exogenous baclofen, ET cells showed no evidence of tonic inhibition by endogenous GABA (Karpuk and Hayar 2008). This suggests that the tonic inhibition across the ON3 ET3 PG circuit is primarily due to tonic GABA B R inhibition at the ON3 ET synapse.…”
Section: Tonic Gaba B R-dependent Presynaptic Inhibition Of On Terminalsmentioning
confidence: 88%
“…The use of I–V slopes represents the most precise method to calculate input conductance or resistance, since several recordings with different voltages and currents are included into the linear regression algorithm, which minimizes calculation errors (Karpuk and Vorobyov, 2003; Mishima et al, 2007; Karpuk and Hayar, 2008). Cell membrane capacitance (Cm) was calculated using the definition of time constant, t=RC, where t was the time constant calculated by the declining membrane potential at 5–20 mV from resting membrane potential (RMP) (i.e.…”
Section: Methodsmentioning
confidence: 99%